Establishment of Complex Modulus Master Curves Based on Generalized Sigmoidal Model for Freeze–Thaw Resistance Evaluation of Basalt Fiber-Modified Asphalt Mixtures - Tan, Guojin (Polymers (Basel), 2020)
This study aims to study the freeze–thaw (F–T) resistance of asphalt mixture incorporating styrene–butadiene–styrene (SBS) polymer and basalt fiber by using the established complex master curves of the generalized Sigmoidal model. Asphalt mixture samples incorporating styrene–butadiene–styrene (SBS) polymer and basalt fiber were manufactured following the Superpave gyratory compaction (SGC) method and coring as well as sawing. After 0–21 F–T cycles processing, a complex modulus test asphalt mixture specimen was performed to evaluate the influence of the F–T cycle. Besides, according to the time–temperature superposition principle, the master curves of a complex modulus were constructed to reflect the dynamic mechanical response in an extended range of reduced frequency at an arbitrary temperature. The results indicated that the elastic and viscous portions of asphalt mixture incorporating SBS and basalt fiber have decreased overall. It could be observed from the dynamic modulus ratio that the dynamic modulus ratios of specimens were more affected by the F–T cycle at low frequency or high temperature. Thus, in the process of asphalt pavement design and maintenance, attention should be paid to seasonal frozen asphalt pavement under low frequency and high temperature.